2016
DOI: 10.1016/j.drugalcdep.2016.02.036
|View full text |Cite|
|
Sign up to set email alerts
|

Ibudilast attenuates subjective effects of methamphetamine in a placebo-controlled inpatient study

Abstract: Background Despite numerous clinical trials no efficacious medications for methamphetamine (MA) have been identified. Neuroinflammation, which has a role in MA-related reward and neurodegeneration, is a novel MA pharmacotherapy target. Ibudilast inhibits activation of microglia and pro-inflammatory cytokines and has reduced MA self-administration in preclinical research. This study examined whether ibudilast would reduce subjective effects of MA in humans. Methods Adult, non-treatment seeking, MA-dependent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 34 publications
1
42
1
Order By: Relevance
“…While modulation of glutamatergic neurotransmission is not a primary mechanism of ibudilast action, this effect may be significant given that the expression of cocaine sensitization is associated with increased nucleus accumbens glutamate levels following cocaine challenge during abstinence (Pierce et al, 1996). Taken together, it is not yet clear which of ibudilast's many actions are responsible for the reduction in drug-stimulated behaviors seen here and in other studies (Hutchinson et al, 2009; Beardsley et al, 2010; Snider et al, 2012; Snider et al, 2013; Bell et al, 2015; Worley et al, 2016). Thus, now that a role for ibudilast in reducing cocaine-mediated behavior has been established by the present work, further study is needed to precisely delineate the underlying mechanism(s).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…While modulation of glutamatergic neurotransmission is not a primary mechanism of ibudilast action, this effect may be significant given that the expression of cocaine sensitization is associated with increased nucleus accumbens glutamate levels following cocaine challenge during abstinence (Pierce et al, 1996). Taken together, it is not yet clear which of ibudilast's many actions are responsible for the reduction in drug-stimulated behaviors seen here and in other studies (Hutchinson et al, 2009; Beardsley et al, 2010; Snider et al, 2012; Snider et al, 2013; Bell et al, 2015; Worley et al, 2016). Thus, now that a role for ibudilast in reducing cocaine-mediated behavior has been established by the present work, further study is needed to precisely delineate the underlying mechanism(s).…”
Section: Discussioncontrasting
confidence: 56%
“…Ibudilast was also found to block the development of methamphetamine sensitization in male mice (Snider et al, 2012). More recently, ibudilast was shown to reduce the reward-related subjective effects of methamphetamine (Worley et al, 2016). These data are supported by work of Becker and colleagues, which found that ibudilast reduced ethanol self-administration in non-dependent male rats as well as in dependent male mice (Bell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I clinical trial involving the PDE4 inhibitor ibudilast was recently completed but has not yet been reported. A recent placebo-controlled trial found that ibudilast reduced some of the subjective reward effects of methamphetamine (Worley et al, 2016). PPARγ agonists, historically used for the treatment of type II diabetes, might also be helpful in alcohol use disorders through their anti-inflammatory activities.…”
Section: New Treatments Strategies Based On Immune Pharmacologymentioning
confidence: 99%
“…Ibudilast was safe and well tolerated in combination with IV methamphetamine (DeYoung et al, 2016). Worley and colleagues (2016) examined whether ibudilast would reduce subjective effects of methamphetamine among non-treatment seeking, methamphetamine-dependent volunteers (n=11). Using a within-subjects design, the subjective effects of IV methamphetamine (15 mg, 30 mg) were examined using a visual analog scale (VAS), following 7 days of maintenance on placebo, moderate-dose ibudilast (40 mg, BID), and high-dose ibudilast (100 mg, BID).…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%